A General, Analytical Model for Flow Battery Costing and Design. Issue 10 (19th July 2018) - Ma, Rose X.; Setzler, Brian P.; Gong, Ke; Gu, Shuang; Yan, Yushan
Abstract : We expound a versatile analytical model to characterize redox flow batteries (RFBs) from the cell to stack scales. It is validated against measurements of our own RFB, zinc-ferricyanide, as well as against those from the literature of competitive RFBs. We also put forth a heuristic framework for optimization of capital cost and design parameters, as well as consequent findings: that modeling enables even-handed comparison of even pre-commercial RFB concepts, with zinc/ferricyanide as the most cost-effective candidate so far; and that overpotential characteristics and engineering strategies are highly RFB dependent, but readily probed by a robust model.